PENGARUH BEBAN KERJA, DISIPLIN KERJA, DAN IKLIM ORGANISASI TERHADAP KOMITMEN ORGANISASI PERANGKAT DESA SE-KECAMATAN BOJONGSARI KABUPATEN PURBALINGGA - Farhan Sofyan Dermawan; Hengky Widhiandono; Suyoto Suyoto; Alfalisyado Alfalisyado (Universitas Bina Taruna Gorontalo, 2024)
This investigation examines the impact of workload, work discipline, and organizational climate regarding the village's structural dedication organizational apparatus in the Bojongsari Sub-district. This study method is quantitative to test the relationship between variables. The population in this research was 117 village officials in Bojongsari District. Sampling technique using quota. The data collection instrument used a five-level Likert scale questionnaire. The analysis tool uses Smart PLS. The findings found that workload has a positive impact and has no negative influence on Organisational Commitment. Work discipline has a positive impact on positive but negligible effects are seen on commitment to the organization from the environment and commitment to the company.